How Coordination Mechanisms Shape Blended-Finance Design and Implementation to Mobilize Private Investment for Sustainable Development in Egypt - Al Nahari, Sundus Abdulmalik (AUC Knowledge Fountain, 2026)
Blended finance is widely promoted as a mechanism to mobilize private capital for climate and green development in developing and emerging economies, yet its performance often falls short of its transformative promise. While concessional loans, guarantees, grants, and technical assistance are intended to improve risk–return profiles and crowd in private investment, gaps in coordination and transparency can undermine additionality, weaken accountability, and create risks of market distortion or subsidy dependence. These challenges are amplified in multi-actor delivery chains where donors, development finance institutions (DFIs), public entities, intermediaries, and private actors operate with different mandates, risk perceptions, and information systems. This thesis examines how coordination mechanisms shape blended-finance design and implementation to mobilize private investment for sustainable development in Egypt. Adopting a qualitative, exploratory research design, the study focuses on operational governance within blended-finance delivery chains, delegated roles and decision rights, decision sequencing and screening “gates,” managed information flows, and accountability arrangements. Evidence is drawn from semi-structured interviews and analyzed through a combined interpretive lens of Transaction Cost Economics (TCE) and polycentric climate governance (PCG), situated within an extensive review of climate and blended finance literature. The analysis addresses: (i) how coordination structures information production and decision-making, (ii) how coordination shapes instrument design and implementation features (e.g., eligibility parameters, concessionality, risk-sharing tools, and technical assistance), and (iii) how safeguards discipline concessionality and protect additionality. Findings show that blended finance mobilizes private investment when coordination mechanisms construct a feasibility pathway across the delivery chain with three interlocking functions. First, delegated roles and reporting routines stabilize decision rights and accountability across multiple decision centers. Second, eligibility infrastructure, pipeline-building, technical assistance, and business-case translation reduce uncertainty and transaction costs, making private participation implementable under real market conditions. Third, embedded safeguards, including targeting, conditional incentives, third-party verification, and thresholds, protect integrity, constrain market distortion, and limit dependence as concessional layers. The thesis contributes an empirically grounded account of blended-finance delivery in Egypt and highlights practical implications for designing coordination and assurance routines that mobilize private capital credibly while maintaining additionality.